Komunikasi Antarbudaya Dalam Mobilitas Global: Studi Adaptasi Mahasiswa Indonesia Di Jerman - Pratiwi, Sitta Channa; Laksono, Puji (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
Germany is a country with an advanced education system that attracts many Indonesian students to continue their studies. Differences in culture, language, and social norms often become challenges in the adaptation process. Indonesian students tend to have less understanding of the importance of intercultural communication as a determinant of successful adaptation in a new environment. This study aims to examine the intercultural communication strategies used by Indonesian students in Germany to support the social adaptation process. The study used a qualitative method with data collection techniques in the form of interviews, documentation, and literature studies. Culture shock theory was used to understand the dynamics of adaptation, while the AGIL (Adaptation, Goal Attainment, Integration, Latency) scheme from Talcott Parsons was used to analyze communication adaptation strategies. The results of the study showed that cultural and social differences between Indonesia and Germany were often not predicted in advance by students, resulting in communication barriers, stereotypes, and difficulties in social interaction. The adaptation process takes place through direct experience that encourages students to develop new communication patterns, strengthen cross-cultural understanding, and build social networks. The right adaptation strategy has been shown to accelerate adjustment and support academic and social success. These findings emphasize the importance of readiness in intercultural communication to improve the successful adaptation of Indonesian students who continue their studies abroad.